Entrepreneurial orientation and the efficiency of SMEs: The role of government financial incentives in an emerging industry. Issue 3 (29th July 2020) - Khattak, Muhammad Sualeh; Shah, Syed Zulfiqar Ali
Abstract : This study examines the moderating role of government financial incentives on the relationship between each dimension of entrepreneurial orientation (i.e., innovativeness, proactiveness and risk‐taking) on the efficiency of SMEs. Data were collected through a structured questionnaire using a sample size of 260 SMEs operating in Pakistan, an emerging economy. The findings indicate that two dimensions of entrepreneurial orientation (i.e., innovativeness and proactiveness) have a significant positive impact on SMEs' efficiency but risk‐taking has an insignificant influence on the efficiency of SMEs. Furthermore, government financial incentives significantly strengthen the relationship of innovativeness and efficiency as well as between risk‐taking and efficiency. Surprisingly, the relationship between innovativeness and efficiency is not significantly tighter by government financial incentives in emerging SMEs. This study recommends that SMEs need to emphasize innovative and proactive entrepreneurial activities. This study also suggested that in particular, risk‐averse owners and managers should build strong ties with the government to access financial resources, so they will likely take the risk and invest enough capital in several projects. Moreover, our research advises the government to facilitate SMEs to boost the industrial growth that will result in high economic growth.